2015
DOI: 10.1016/j.rpped.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Medidas de localização da gordura corporal: uma avaliação da colinearidade com massa corporal, adiposidade e estatura em adolescentes do sexo feminino

Abstract: OBJECTIVE: To verify the correlation between body fat location measurements with the body mass index (BMI), body fat percentage (BF%) and height, according to the nutritional status in female adolescents. METHODS: A controlled cross-sectional study was carried out with 113 adolescents (G1: 38 with normal weight, but with high body fat level, G2: 40 with normal weight and G3: 35 overweight) from public schools in Viçosa-MG, Brazil. The following measures were assessed: weight, height, waist circumference (WC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 25 publications
4
10
0
14
Order By: Relevance
“… 15 Body mass index, an indicator widely used in pediatric clinical practice for the assessment of nutritional status, showed a worse performance than waist circumference and waist/height ratio, which is consistent with previous studies that demonstrated the superiority of waist circumference as an isolated measure or adjusted by height. 13 , 25 , 28 Additionally, waist circumference is less affected than body mass index by gender, ethnicity, and total fat. 28 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 15 Body mass index, an indicator widely used in pediatric clinical practice for the assessment of nutritional status, showed a worse performance than waist circumference and waist/height ratio, which is consistent with previous studies that demonstrated the superiority of waist circumference as an isolated measure or adjusted by height. 13 , 25 , 28 Additionally, waist circumference is less affected than body mass index by gender, ethnicity, and total fat. 28 …”
Section: Discussionmentioning
confidence: 99%
“… 22 Differences in MS and HW phenotype prevalence can be attributed to variations in the cutoffs used to classify central obesity, hypertriglyceridemia, and other components of MS between different studies and their differences regarding nutritional status, sexual maturation, race/ethnicity and life habits between regions. 12 , 25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Klasifikasi obesitas di Indonesia mengikuti kriteria dari Riskesdas yaitu individu dengan IMT ≥ 27. [3][4][5] Obesitas terjadi karena ketidakseimbangan energi dalam jangka waktu lama dimana asupan energi (dalam bentuk makanan) lebih besar dibandingkan pengeluarannya. Salah satu cara untuk mencegah terjadinya obesitas adalah dengan mengatur pengeluaran energi.…”
Section: Original Articleunclassified